Correlation of morphologic findings and apparent diffusion coefficient values with Ki-67 proliferation index in patients with glioblastoma - Öncü, Süleyman; Şerifoğlu, İsmail and Arslan, Fatma Zeynep and Karagülle, Mehmet and Şimşek, Samet and Kaya, Gül Gizem and Cimilli, Ahmet Tan (The European Research Journal, 2022)
Objectives: Glioblastoma is the most common primary neoplasm of the central nervous system (CNS) and has a very poor prognosis. Ki-67 proliferative index is a value that reflects the mitotic index of the tumor and is associated with poor prognosis. The radiological features of the tumors can predict the course of the disease. The aim of this study is to evaluate the relationship between the morphology and the apparent diffusion coefficient (ADC) values of the tumor with the Ki-67 index on preoperative magnetic resonance imaging (MRI). Methods: Preoperative MRI images of 52 patients with pathological diagnosis of glioblastoma were evaluated retrospectively. A score ranging from 1 to 3 was assigned to each of the morphological features of the tumors (peritumoral edema, necrosis, contrasting pattern, heterogeneity, hemorrhage, mass effect, tumor contour irregularity), and was added up to obtain the total score. In addition, the ADC values of each tumor were measured at the workstation. ADC value and total score of each tumor, and Ki-67 values obtained histopathologically were compared. Results: There was a negative correlation between Ki-67 index of tumors and ADC values (r=-0.895, p = 0.0001). A significant positive correlation was found between the morphological features of the tumors and their total scores (r=0.772, p = 0.0001). A statistically significant negative correlation was found between total score and ADC values (r=-0.780, p = 0.0001). Heterogeneity and necrosis were the features most closely associated with Ki-67. These were followed by mass effect, hemorrhage and contour irregularity, respectively. Conclusions: The morphological findings and ADC values obtained from preoperative MRI are related to the Ki-67 value, and thus can be used to predict prognosis and guide treatment in the early period.